LIQUID-LIQUID EQUILIBRIA DATA OF N-METHYL-2-HYDROXYETHYL AMMONIUM ALKYLATES WITH BUTANOL+WATER AND PENTANOL+WATER AT 293.15K, 313.15K AND 333.15K - Amorim,Karina S. (2018)
Abstract Ionic liquids (ILs) are organic salts with low volatility and have different applications including organic synthesis, separation and extraction processes, fuel cell electrolyte, surfactants, among others. Protic ILs based on the N-methyl-2-hydroxyethyl ammonium cation and short chain carboxylic anions have simple synthesis and purification. However, as new substances few data are available for their thermodynamic properties and phase equilibria. In order to investigate the partition of these substances in alcohol-water, liquid-liquid equilibria data were determined experimentally for three ionic liquids (formed by the cation N-methyl-2-hydroxyethyl ammonium (m-2HEA) and the anions propionate (Pr), butanoate (B) and pentanoate (P)) with butanol and pentanol, at three different temperatures: 293.15K, 313.15K and 333.15K. The binodal curves are obtained by the turbidity method with gravimetric determination of all the components, curves are fitted using the Merchuk method. The tie-lines are also gravimetrically determined. The results confirm the high hydrophilicity of these ionic liquids, with partition coefficients of water-butanol and water-pentanol lower than 1. Data were correlated with UNIFAC.